Liquid Conductivity Detection by Passive Secure UHF RFID Tag - Yang, Chenwei; Tao, Yonghui; Lan, Tiange; Man, Hui (2018 48th European Microwave Conference (EuMC), 2018)
A passive secure ultra-high frequency (UHF) radio frequency identification (RFID) tag for liquid conductivity detection is here introduced. Products of liquids are plentiful exist and widely used in human's daily life. It will be very helpful for RFID information security enhancement if a RFID tag could be able to detect the mismatching between real product the tag attached on and information recorded in RFID chip. Since liquid can be separated by its conductivity, passive RFID conductivity sensor tags are accordingly desired. For demonstration, a passive UHF RFID sensor tag is designed to detect solution with conductivity of less than 0.5 S/m. Read performance of the tag will degrade rapidly as conductivity varies to less than 0.5 S/m. Agreement between simulated and experimental results reveals the potential of the proposed tag can be extended using in distinguishing many other liquid products.